Analysis of Flexural Strength of Concrete Regarding the Addition of Fly Ash as A Particular Replacement Material for Cement - Zulkarnain, Fahrizal; Al Asri, Ramadhan; Siregar, Zulkifli; Muthusamy, Khairunisa (Jurnal Teknologi, 2025)
This study a number of additional materials were added to reduce the amount of cement by using fly ash from coal combustion to determine the flexural strength value of concrete. Use of fly ash additives 5% 10% 15%. For normal concrete the flexural strength value is 2,66 MPa. For the flexural strength value of concrete with a BFA variation of 5% is 2,67 MPa, For the flexural strength value of concrete with a BFA variation of 10% is 2,71 MPa, and for the flexural strength value of concrete with a BFA variation of 15% is 2,72 MPa. From the results of this study it can be concluded that the more fly ash mixture, the higher the flexural strength value.